Framework for Articulating Beliefs: Reflections on Teaching and Learning Experiences - ARIATNA ARIATNA (BAHAS, 2014)
Our beliefs have a great influence on our daily activities and how we do them, for example how people go about driving has a lot to do with their beliefs about safety, beliefs about health influence the way people drink and eat, etc. As an English practitioner, my teaching practice is also driven by my beliefs. Thus, the way I select materials, start the class, assign an activity, and assess my students are informed by what I believe to be relevant to be applied to my language classroom. In the following paragraphs, I will discuss four categories of the Stern’s framework for articulating teaching beliefs and provide experience-based examples to illustrate how each could inform classroom pedagogy. As an extension of Stern’s view, I will also discuss the importance of assessment for learners and professional development for teachers. At this stage, my views will be based on the experiences that I have acquired as a language learner and a language teaching professional. Key Words: framework, teaching beliefs, classroom pedagogy, teaching experience.